EVALUASI MUTU FISIOLOGIS BENIH KEDELAI KUNING (Glycine max L.) PADA PENYIMPANAN TERBUKA - Ari Wahyuni; Ria Putri; Riana Jumawati; Fetri Pristi Prasinta (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2022)
Quality soybean seeds are one of the essential factors to support soybean production. One of the obstacles in providing quality soybean seeds was the physiological quality of soybean seeds declined speedily during storage, especially in open storage. This study aimed to evaluate the physiological quality of yellow soybean seeds during a six-month storage period. This research was carried out from October 2020 to March 2021 in the seed analysis laboratory of the Seed Technology Study Program, Lampung State Polytechnic. The study used a Split-Plot Completely Randomized Design (CRD) with four replications. The main plot was the seed storage period which consists of seven levels, specifically 0, 1, 2, 3, 4, 5, and 6 months. Sub-plots were soybean variety which consists of two levels, specifically Dega variety and Deja variety. The results of the study indicated that (1) Deja variety had higher physiological quality than Dega variety based on germination, vigor index, growth speed, growth, maximum growth potential, and seed moisture content during the six-month storage period (2) Deja variety had longer storability than Dega variety in open storage.Keywords: Soybean, Physiological quality, Open storage.